Effectiveness of Breast Massage on Breast Engorgement Among Lactating Mothers: A Systematic Review: Effectiveness of Breast Massage on Breast Engorgement Among Lactating Mothers: A Systematic Review - Pingwong , Kridsana; Kantaruksa , Kannika; Chaloumsuk , Nonglak (Nursing Journal CMU, 2020)
Breast engorgement is a problem that is frequently found in lactating mothers and it is a major factor affecting the decision to stop breastfeeding. Breast massage is an effective method for reducing breast engorgement. The purpose of this systematic review was to summarize evidence based about the effectiveness of breast massage on breast engorgement in lactating mothers. The study searched for all published and unpublished randomized controlled trial and quasi-experimental studies in Thai and English regarding the effect of breast massage on breast engorgement from 2010 to 2016. The systematic review was conducted using a systematic guideline developed by the Joanna Briggs Institute (JBI, 2014). All included studies were independently appraised and extracted by the researcher and major advisor using standardized tools, also developed by the Joanna Briggs Institute. There were 2 articles studying the effectiveness of breast massage on breast engorgement in lactating mothers, which met the inclusion criteria and the critical appraisal criteria. One was a randomized controlled trial study while the other was a quasi-experimental study. Data were analyzed using narrative summarization. Due to the difference of intervention, method, and time for measuring outcome in each study, meta-analysis could not be used in this particular study. The result of this systematic review found that there were 2 methods of breast massage reducing breast engorgement in lactating mothers. These were Gua-Sha therapy and Oketani breast massage. Both studies presented clear practice guidelines. When performed gently by trained health professionals, breast massage proved to be an effective intervention. The results of this systematic review found that the Gua-Sha therapy could reduce breast engorgement. The Oketani breast massage could reduce pain in lactating mothers with breast engorgement. These findings suggest that breast massage must be practiced based on clear guidelines and performed gently. Further experimental studies using randomized controlled trial are required in order to provide credible evidence and enough qualified studies to perform meta-analysis.